Impacts of horizontal integration on Czech retail stores with fast-moving goods - Paták, Michal; Branská, Lenka; Pecinová, Zuzana (My University, 2019)
Horizontal integration is currently an opportunity to increase the performance of organizations. While being possible with various entities, it is typical for retail stores and companies that provide paid logistics services. The literature deals with the benefits of horizontal integration and barriers to implementation. So far, however, it has not addressed the results of horizontal integration, i.e. perception of their advantages and disadvantages after the integration process. The paper expands the theoretical knowledge in the field of disadvantages of implemented horizontal integration. It presents the results of primary quantitative research carried out in 142 retail stores. Managers of integrated stores consider the limited influence on the type and breadth of the assortment sold as well as on the setting of prices and margins and the need to adhere to a uniform visual style of the store to be the biggest disadvantages. Managers of independent stores do not perceive the problem of limiting the influence on the type and breadth of the assortment sold so significantly, but much more significantly than managers of integrated stores they see the disadvantage in the lower quality of delivered goods, limited influence on distribution of created financial resources and distortion of market information.
Dopady horizontální integrace na české maloobchodní prodejny s rychloobrátkovým zbožím.
Keywords: supply chain management; retail; horizontal integration; fast-moving consumer goods; dodavatelský řetězec; maloobchod; horizontální integrace; rychloobrátkové zboží